PENGARUH DIKLAT DI TEMPAT KERJA (DDTK) SUBSTANSI PENELITIAN TINDAKAN KELAS (PTK) TERHADAP PEMAHAMAN GURU MADRASAH DALAM PENULISAN PTK DI KABUPATEN BANGKA BELITUNG DAN BELITUNG TIMUR - Lilis Suryani (Lembaga Administrasi Negara, 2018)
Education and Training is a form of institutional intervention so that employees have competency standards so that they are able to carry out their duties properly and appropriately. This study discusses the improvement of teacher competency in the implementation of scientific publications through Training in the Workplace (DDTK) Classroom Action Research (PTK). DDTK aims to improve the technical competence of civil servants and non-civil servants of the ministry of religion according to their duties and positions and develop insight into employee duties related to new regulations / policies / provisions, new technologies, or new knowledge relevant to their main tasks and functions. The main objective of Classroom Action Research (CAR) is the improvement and improvement of learning services. The population and sample of this study were participants of the Madrasah teacher training in the Workplace (DDTK) in Bangka, Belitung, and East Belitung Regencies in the 2016 and 2017. The study used multiple regression using Adjusted Square. Calculations for this multiple regression using SPSS statistical version 16 software. From the results of the research, it was found that the average of DDTK Bangka District Classroom Action Research (PTK) 2016 and 2017 were 51.41, and the average DDTK Class Action Research substance (PTK) Belitung Regency in 2016 and 2017 amounted to 50.39, with a difference in mean scores of 1.02. The average understanding of madrasah teachers in Bangka Regency 2016 and 2017 PTK writing was 118.20, and the average madrasah teacher understanding in Belitung Regency PTK writing in 2016 and 2017 was 118.88, with a mean difference of 0.68. The regression coefficient of the Education and Training Center (DDTK) variable (X2) has a positive sign (0.074), which means that the Education and Training Center (DDTK) variable has a positive influence on teacher understanding. The hypothesis which states that there is an effect of the Workplace Education Training (DDTK) substance on Classroom Action Research (CAR) on the understanding of madrasah teachers in writing PTK is statistically proven. Keywords: Training at Workplace, Classroom Action Research, Teacher's Understanding